Using design thinking to enhance construction site problem solving - Mokhtar, Ehab (AUC Knowledge Fountain, 2016)
Problem solving is one of the most important issues in Construction Management (CM), it influences the outcome of the project due to the amount of decisions and problems that the Construction Manager faces in each project. Construction Management is a vital subject that has been in the spotlight of academic research for decades, which led to its emerging by going through the cycles of developing and evolution. The criteria of decision-making and problem solving have also evolved from focusing on the technical and objective aspects of construction to the soft and subjective ones. (Bakht, El Diraby 2015). Nevertheless, the last two decades saw the rise of “Design Thinking” as a new approach for innovation and solving problems in a creative way, it is an approach calls for adapting more subjective, human and innovative problem solving. Design Thinking was adapted in many aspects of social and business life with a great success (Lidtkaj 2014), however, no enough attention were given to it in the construction industry, which gives this research a special importance. In this research, I am trying to examine the efficiency of adapting Design Thinking in solving problems in the construction sites, by means of conducting an experiment to examine whether Design Thinking will enhance problem solving or not. Three simple problems were presented to multidisciplinary 21 participants, they were asked to solve these problems with their traditional (rule-of-thumb) method. Subsequently, they were given a training session on Design Thinking, then they were asked to form small groups to work on the same problems again but this time by using what they have learnt in the Design Thinking session. The experiment showed a great acceptance and understanding to this approach from the participants, over and above, the results have shown a significant enhancement in problem solutions resulted from Design Thinking session compared to traditional method one. The results are encouraging for more research on how we can adapt Design Thinking approach in construction industry, since it proved to have the potential in helping developing Construction Management.